Predictors of adverse prognosis in COVID‐19: A systematic review and meta‐analysis. (27th August 2020) - Figliozzi, Stefano; Masci, Pier Giorgio; Ahmadi, Navid; Tondi, Lara; Koutli, Evangelia; Aimo, Alberto; Stamatelopoulos, Kimon; Dimopoulos, Meletios‐Athanasios; Caforio, Alida L. P.; Georgiopoulos, Georgios
Abstract: Background: Identification of reliable outcome predictors in coronavirus disease 2019 (COVID‐19) is of paramount importance for improving patient's management. Methods: A systematic review of literature was conducted until 24 April 2020. From 6843 articles, 49 studies were selected for a pooled assessment; cumulative statistics for age and sex were retrieved in 587 790 and 602 234 cases. Two endpoints were defined: (a) a composite outcome including death, severe presentation, hospitalization in the intensive care unit (ICU) and/or mechanical ventilation; and (b) in‐hospital mortality. We extracted numeric data on patients' characteristics and cases with adverse outcomes and employed inverse variance random‐effects models to derive pooled estimates. Results: We identified 18 and 12 factors associated with the composite endpoint and death, respectively. Among those, a history of CVD (odds ratio (OR) = 3.15, 95% confidence intervals (CIs) 2.26‐4.41), acute cardiac (OR = 10.58, 5.00‐22.40) or kidney (OR = 5.13, 1.78‐14.83) injury, increased procalcitonin (OR = 4.8, 2.034‐11.31) or D‐dimer (OR = 3.7, 1.74‐7.89), and thrombocytopenia (OR = 6.23, 1.031‐37.67) conveyed the highest odds for the adverse composite endpoint. Advanced age, male sex, cardiovascular comorbidities, acute cardiac or kidney injury, lymphocytopenia and D‐dimer conferred an increased risk of in‐hospital death. With respect to the treatment of the acute phase, therapy with steroids was associated with the adverse composite endpoint (OR = 3.61, 95% CI 1.934‐6.73), but not with mortality. Conclusions: Advanced age, comorbidities, abnormal inflammatory and organ injury circulating biomarkers captured patients with an adverse clinical outcome. Clinical history and laboratory profile may then help identify patients with a higher risk of in‐hospital mortality.